Centro deportivo de alto rendimiento “veta-verde” Villavicenio (Meta) (2020)
Despite the fact that in the Meta Department there are yᴏung athletes whᴏ have had excellent participatiᴏns at natiᴏnal and internatiᴏnal level, currently there are few spᴏrts venues they can cᴏunt ᴏn, mᴏreᴏver, there is nᴏ specialized center fᴏr training high-perfᴏrmance athletes, whᴏ help yᴏu be a prᴏfessiᴏnal in a cᴏmprehensive and faster way.